Intensity of Powdery Mildew in Soybean Under Changes of Temperature and Leaf Wetness - Alves, Marcelo de C.; Pozza, Edson A.; Costa, João de C. do B.; Ferreira, Josimar B.; Araújo, Dejânia V. de; Carvalho, Luiz Gonsaga de; Silva, Fábio Moreira da; Sanches, Luciana (IntechOpen, 2011)
None